2021
DOI: 10.1590/1414-431x2021e11459
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA has_circ_0001806 promotes hepatocellular carcinoma progression via the miR-193a-5p/MMP16 pathway

Abstract: Reportedly, circular RNAs (circRNAs) are crucial regulators in cancer progression. Nonetheless, the molecular mechanism of circRNAs in hepatocellular carcinoma (HCC) has not been fully clarified. Gene expression omnibus (GEO) database was employed to screen out the differentially expressed circRNAs in HCC. qRT-PCR and western blot were executed to detect circ_0001806 expression, miR-193a-5p expression, and MMP16 mRNA and protein expressions in HCC. The effect of circ_0001806 on HCC was analyzed by the CCK-8 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…circRNAs exert ubiquitous biological functions in various tissues and cells ( 13 , 14 , 28 ). They have recently been reported as a unique class of long noncoding RNAs that affect the expression of a target miRNA and thereby regulate mRNA expression and influence many biological processes ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs exert ubiquitous biological functions in various tissues and cells ( 13 , 14 , 28 ). They have recently been reported as a unique class of long noncoding RNAs that affect the expression of a target miRNA and thereby regulate mRNA expression and influence many biological processes ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cells and tissue specimens were subjected to RIPA Lysis Buffer (Beyotime) treatment for the isolation of total proteins. 29 The protein concentrations were assessed with the aid of a BCA Protein Assay Kit (Beyotime). Electrophoresis of the total protein was accomplished on an SDS-PAGE gel before the separated proteins were transplanted onto PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…As to hsa-miR-193a-5p in other cancers, there have been a lots of special research reports, like, on ovarian cancer, [75,76] on lung cancer, [77,78] on breast cancer [79][80][81][82] on melanoma, [83] on hepatoblastoma, [84] on esophageal squamous cell carcinoma, [85] on gastric cancer, [86,87] on rhabdomyosarcoma, [88] on papillary thyroid carcinoma, [89] on colorectal cancer, [90][91][92][93][94][95] on cervical cancer, [96,97] on nasopharyngeal carcinoma, [98] on acute myeloid leukemia, [99] on clear-cell renal cell carcinoma, [100] on pancreatic cancer, [101,102] on glioma, [103] on pediatric chordomas, [104] on bladder cancers, [105] on osteosarcoma, [106,107] on prostate cancer, [108][109][110] and on HCC. [111][112][113] Among those special research reports on non-EC cancers, most showed that the effects of hsa-miR-193a-5p on the relative cancers were negatively oncogenic, as hsa-miR-193a-5p was a potential tumor suppressor. [75][76][77][78]…”
Section: The Potential Values Of Exosomal Hsa-mir-193a-5p In Ecmentioning
confidence: 99%